Reframing English teacher identity through pedagogy of disjuncture and critical incidents in global Englishes - Maharsi, Ista; Imelwaty, Sri; Perpisa, Lili; Ramadhanti, Dina; Arumaisya, Syifana (Journal of English and Education (JEE), 2025)
Global Englishes (GE) has challenged long-standing native-speaker norms by affirming the legitimacy of diverse English varieties, yet its classroom implementation remains limited. This article introduces the pedagogy of disjuncture as a conceptual response to this gap. Building on transformative learning theory, it redefines disjuncture as a deliberate pedagogical resource rather than as an obstacle. The core idea of this approach is designed for disjuncture. Unlike traditional uses of Critical Incidents, which often depend on retrospective accounts of classroom experiences, designed disjuncture is intentionally created encounters that expose teachers to linguistic diversity, communicative breakdowns, or intercultural tensions. By structuring these incidents as planned interventions, teacher education can guide participants through cycles of exposure, reflection, and dialogue that lead to the reshaping of professional identity. The contribution of this article is twofold. Conceptually, it combines GE, teacher identity research, and transformative learning into a cohesive framework that broadens the scope of Critical Incident pedagogy. Practically, it outlines how designed disjuncture can be integrated into teacher education curricula worldwide, helping teachers move beyond rhetorical acceptance of GE toward resilient, critically aware professional identities suited for multilingual classrooms.